Oviposition by Spodoptera exigua on Solanum dulcamara Alters the Plant’s Response to Herbivory and Impairs Larval Performance - Geuss, Daniel (Int J Mol Sci, 2018)
Plant resistance traits against insect herbivores are extremely plastic. Plants respond not only to the herbivory itself, but also to oviposition by herbivorous insects. How prior oviposition affects plant responses to larval herbivory is largely unknown. Combining bioassays and defense protein activity assays with microarray analyses and metabolite profiling, we investigated the impact of preceding oviposition on the interaction of Solanum dulcamara with the generalist lepidopteran herbivore Spodoptera exigua at the levels of the plant’s resistance, transcriptome and metabolome. We found that oviposition increased plant resistance to the subsequent feeding larvae. While constitutive and feeding-induced levels of defensive protease inhibitor activity remained unaffected, pre-exposure to eggs altered S. dulcamara’s transcriptional and metabolic response to larval feeding in leaves local and systemic to oviposition. In particular, genes involved in phenylpropanoid metabolism were more strongly expressed in previously oviposited plants, which was reflected by reciprocal changes of primary metabolites upstream and within these pathways. Our data highlight that plants integrate signals from non-threatening life stages of their natural enemies to optimize their response when they become actually attacked. The observed transcriptional and metabolic reshaping of S. dulcamara’s response to S. exigua herbivory suggests a role of phenylpropanoids in oviposition-primed plant resistance.